Develop a Relationship of Shear Strength of Reinforced Concrete Beams with Carbon Fiber CF - جحجاح غاندي; أصلان طارق; بديع رامية (Latakia University Journal -Engineering Sciences Series, 2021)
This research Presents an experimental and analytical study. The experimental consists of a study of shear behavior for concrete beams reinforced with add carbon fibers to the concrete of beams that do not contain transverse stirrups to study their effect on the shear strength of the concrete beams, as it resulted from the study that the carbon fibers added to the concrete mix improved the shear behavior of the concrete beams and increased shear strength, The addition of carbon fibers increased the failure load by (10.8-32.3)% compared to the non-fiber reinforced beam. The analytical component of the research includes developing the relationship of shear strength to the beams reinforced with carbon fibers, depending on the results of the experimental study of the research and previous research using statistical analysis.